Pengaruh Persepsi, Motivasi, dan Minat terhadap Pilihan Berkarir dibidang Perpajakan - Sri Indra Yuni (Pusat Riset dan Inovasi Nasional, 2025)
The aim of this research is to determine the influence of students' perceptions, motivation, interests and knowledge about taxes on career choices in the field of taxation. The formulation of the problem in this research is whether the influence of variables X and Y both have a significant effect. The results of the research are useful for interested parties, namely Muhammadiyah University, especially the Accounting study program, in increasing perception, motivation and interest in career choices in the field of taxation. This research was carried out at the Faculty of Economics, Muhammadiyah University of Riau. This research sample used a purpose sampling technique, namely Accounting students in 2020 and 2021 with a population of 196 students and a research sample of 66 students was taken from the Slovin formula. This research instrument uses a questionnaire and is tested with validity, reliability, regression analysis and hypothesis testing (t test) using the SPSS application. The results of this research are that perceptions influence career choices in the field of taxation, this is because one person's form of assessment in facing perceptual stimuli is the same, but in other conditions it will give rise to different perceptions. Motivation does not influence the choice of a career in taxation, indicating that students' motivation to pursue a career in taxation is very low for individuals who have a career in taxation. Interest influences the choice of a career in taxation. This is due to observations and considerations that a career in taxation will provide something positive to individuals which creates a desire to have a career in taxation.